The Electric Bicycle: Worldwide Research Trends - Salmeron-Manzano, Esther; Manzano-Agugliaro, Francisco (Energies (Basel), 2018)
The bicycle has gone from being an old-fashioned recreational product to a less polluting means of transport and a compact, ultra-light personal mobility tool. This is how electrical bicycles will be used as the pillar that could support individual public transport in large cities worldwide. The objective of this manuscript is to detect how worldwide research on the electric bicycle is being developed, and, especially, around which scientific domains is it clustered, to finally identify the main trends in the field. This study has been carried out based on the Scopus database, where all the publications related to the topic of the electric bicycle have been analyzed up to the year 2017. ¨Therefore, research on the global research trends of this topic was conducted. Its evolution over time shows that since 2008 the growth of publications is much higher than in the previous period. The main countries are China and the USA, and it can be inferred that there are two major trend countries with high environmental awareness, which also have a large population and that the electric bicycle is a suitable and sustainable form of transport. Among the main scientific fields, engineering leads in research. The keyword analysis shows that the central theme is electric, then battery and motor stand out. A community detection was applied to detect the six main clusters of this research, largely dedicated to the following topics: Transportation–Environment, Electrical Engineering, Safety, Batteries, Sporting Goods–Urban Planning, and Mechanical Engineering. This manuscript shows that global research trends about the electric bicycle are increasing, and that it should be considered a means of sustainable urban transport and will therefore contribute to energy saving and sustainable energy.